Rare Variants of the Serotonin Transporter Are Associated With Psychiatric Comorbidity in Irritable Bowel Syndrome. (July 2016) - Kohen, Ruth; Tracy, Julia H.; Haugen, Eric; Cain, Kevin C.; Jarrett, Monica E.; Heitkemper, Margaret M.
Alterations in serotonin signaling are suspected in the pathophysiology of irritable bowel syndrome (IBS). By modulating the extracellular reuptake of serotonin, the serotonin transporter (SERT) acts as a key regulator of the bioavailability of serotonin. This study is the first to investigate the impact of rare SERT variants (i.e., those with a minor allele frequency of < 1%) on the risk for IBS, gastrointestinal (GI) symptom level, response to cognitive–behavioral treatment, and psychiatric comorbidity. We sequenced a 0.19 megabase chromosomal stretch containing the SERT gene and surrounding regions in a community sample of 304 IBS patients and 83 controls. We found no significant associations between rare variants in and around the SERT gene and IBS risk, GI symptom profile, or response to treatment. We found preliminary evidence, however, that IBS subjects with a history of either depression or anxiety were significantly more likely to carry multiple rare likely functional variant alleles than IBS patients without psychiatric comorbidity.